Pubertal and gonadal outcomes in 46,XY individuals with partial androgen insensitivity syndrome raised as girls - GÜRAN, TÜLAY (My University, 2023)
Introduction: Although it was common in the 1970s-1990s to assign female gender of rearing to 46,XY infants with limited virilization of varying etiologies, including those with partial androgen insensitivity syndrome (PAIS), long-term data on outcomes for these individuals are sparse. Therefore, our goal was to use the power of an international registry to evaluate clinical features, surgical management, and pubertal data in patients with a molecularly confirmed diagnosis of PAIS who were born before 2008 and were raised as girls. Methods: The current study interrogated the International Disorders of Sex Development Registry for available data on management and pubertal outcomes in individuals with genetically confirmed PAIS who were raised as girls. Results: Among the 11 individuals who fulfilled the key criteria for inclusion, the external masculinization score (EMS) at presentation ranged from 2 to 6 (median 5); 7 girls underwent gonadectomy before the age of 9 years, whereas 4 underwent gonadectomy in the teenage years (>= age 13). Clitoral enlargement at puberty was reported for 3 girls (27%) who presented initially at the time of puberty with intact gonads. In the 9 individuals (82%) for whom gonadal pathology data were provided, there was no evidence of germ cell tumor at median age of 8.1 years. All girls received estrogen replacement, and 8/11 had attained Tanner stage 4-5 breast development at the last assessment. Conclusion: In general, although it appears that female assignment in PAIS is becoming uncommon, our data provide no evidence to support the practice of prophylactic prepubertal gonadectomy with respect to the risk of a germ cell tumor.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Mikrobiyal Genetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Microbial Genetics; Natural Sciences; GELİŞİMSEL BİYOLOJİ; Yaşam Bilimleri (LIFE); DEVELOPMENTAL BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Embriyoloji; Moleküler Biyoloji; Gelişimsel Biyoloji; Sağlık Bilimleri; Embryology; Molecular Biology; Developmental Biology; Health Sciences; Puberty; Androgen insensitivity syndrome; Partial androgen insensitivity syndrome; Disorders of sex development; Differences of sex development; RECEPTOR GENE-MUTATIONS; GERM-CELL TUMORS; CONSENSUS STATEMENT; SEX; DISORDERS; FERTILITY; PATIENT; GONADECTOMY; MANAGEMENT; PHENOTYPE